Do family characteristics contribute to a socioeconomic gradient in overweight in early childhood?: single mediation analyses of data from German preschool children - Hoffmann, Stephanie; Sander, Lydia; Rattay, Petra; Blume, Miriam; Hövener, Claudia; Schneider, Sven; Richter, Matthias; Pischke, Claudia R.; Schüttig, Wiebke; De Bock, Freia; Spallek, Jacob (Preventive Medicine Reports, 2023)
Children’s overweight is strongly associated with family socioeconomic position (SEP) and family characteristics (FC). There is limited research on the extent to which FC account for a socioeconomic gradient in childhood overweight. This study examined whether FC explain SEP differences in the prevalence of overweight. The study used baseline data of preschool-aged children from the German ‘PReschool INtervention Study’. The sample (n = 872, 48% girls) was recruited at kindergartens in Baden-Württemberg, Germany. Data included children’s measured weight status and parents’ reports on socioeconomic indicators (e.g., school education, vocational education, income) and FC. Variables represent main determinants of overweight (nutrition: sweets consumption in front of TV, soft drink consumption, regular breakfast, child sets table; physical activity: outdoor sports; parental role model). In single mediation analyses indirect effects of SEP on overweight were analysed (OR[95%CI]). Preschool girls and boys with low parental education had higher odds for overweight than children with high parental education. Among boys, low levels of parental education contributed to the odds of overweight via indirect effects by both factors ‘sweets consumption in front of TV’ (OR = 1.31[1.05-1.59]) and ‘no sports’ (OR = 1.14[1.01-1.38]). Among girls, FC measured did not explain SEP differences in overweight. Family nutrition and parental/family physical activity contribute to inequalities in overweight among preschool boys, but not girls. Research is needed to identify FC that explain inequalities in overweight for both.
Online verfügbar: 17. März 2023, Artikelversion: 23. März 2023
Gesehen am 29.08.2024